MODERASI BERAGAMA DI KALANGAN MUDA (STUDI KASUS PEMAHAMAN MODERASI BERAGAMA DI KALANGAN MAHASISWA PADA PERGURUAN TINGGI DI CIREBON) - Ayub Al Ansori; Wahyono Wahyono; Egi Gunawan (Oasis : Jurnal Ilmiah Kajian Islam, 2021)
This article aims to find out the understanding of religious moderation students in the university in Cirebon, to find out the patterns used by the student driving factors in implementing the values of religious moderation in the University environment and to find out the driving factors for students in implementing the values of religious moderation in the University environment. The writer uses a descriptive qualitative research where in this study the researcher examines the participant's perspective with an interactive and flexible strategy. In the context of Indonesian-Islamic thought, the concept of Islamic moderation has five characteristics. First, non-violent ideology in spreading Islamic teachings, adopting modern life patterns such as science and technology, human rights, and democracy. Third is the use of rational thinking in exploring and understanding Islamic teachings. Fourth, the contextual approach is prioritized in understanding the sources of Islamic teachings. Fifth is the use of the ijtihad method in legal istinbat (establishing Islamic law). The results obtained from this study are the Islamic paradigm in which Rahmatan Lil'alamin is the foundation of religious moderation among students in Cirebon. Through the five characteristics of religious moderation and the Islamic paradigm of Islam, Rahmatan Lil'alamin is expected to form students who think moderately and have high tolerance.